2018
DOI: 10.1111/jdi.12837
|View full text |Cite
|
Sign up to set email alerts
|

Non‐high‐density lipoprotein cholesterol is more informative than traditional cholesterol indices in predicting diabetes risk for women with normal glucose tolerance

Abstract: Aims/IntroductionLimited data are available regarding the performance of non‐high‐density lipoprotein cholesterol (non‐HDL) in predicting incident diabetes. We aimed to analyze the association between non‐HDL and development of diabetes, and to estimate the cut‐off point of non‐HDL for discriminating incident diabetes in people with normal glucose tolerance.Materials and MethodsOf 3,653 middle‐aged and elderly Chinese with normal glucose tolerance at enrollment, 1,025 men and 1,805 women returned to the 3‐year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…After administering UA for 15 weeks, the average body weight, liver weight, and epididymal and perirenal adipose contents significantly reduced in the UA (at 100 mg/kg) group by 22.7%, 28%, 27.2%, and 52.1% compared with the HFD group, respectively (all P < 0.05). Non‐HDL‐C is considered to be an important risk factor for predicting obesity‐related chronic diseases and is superior to low‐density lipoprotein cholesterol in disease assessment (Liu et al., 2018; Ramjee, Sperling, & Jacobson, 2011; Verbeek, Hovingh, & Boekholdt, 2015). Therefore, the serum levels of TC, TG, HDL‐C, and non‐HDL‐C and the TC and TG contents in liver tissue were tested to evaluate the lipid‐lowering effect of UA (Table 4).…”
Section: Resultsmentioning
confidence: 99%
“…After administering UA for 15 weeks, the average body weight, liver weight, and epididymal and perirenal adipose contents significantly reduced in the UA (at 100 mg/kg) group by 22.7%, 28%, 27.2%, and 52.1% compared with the HFD group, respectively (all P < 0.05). Non‐HDL‐C is considered to be an important risk factor for predicting obesity‐related chronic diseases and is superior to low‐density lipoprotein cholesterol in disease assessment (Liu et al., 2018; Ramjee, Sperling, & Jacobson, 2011; Verbeek, Hovingh, & Boekholdt, 2015). Therefore, the serum levels of TC, TG, HDL‐C, and non‐HDL‐C and the TC and TG contents in liver tissue were tested to evaluate the lipid‐lowering effect of UA (Table 4).…”
Section: Resultsmentioning
confidence: 99%
“…A case-control study conducted in Han Chinese individuals supported our results, which showed that non-HDL-C is elevated in adults with prediabetes [ 30 ]. However, a cohort study previously proposed that non-HDL-C was more informative than traditional cholesterol indices in predicting the risk of diabetes for women but not for men with NGT, which demonstrated that cholesterol levels might be a sex-specific risk factor for diabetes [ 31 ]. In addition, our study showed that the AUC of non-HDL-C (0.705) was larger than that of the TG/HDL-C and TC/HDL-C ratios (0.692 and 0.686 respectively) to discriminate diabetes, which was inconsistent with an investigation in Tangshan, China [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Non-HDL cholesterol was previously reported to show a better performance for predicting diabetes than total, HDL, and LDL cholesterols in Canadian and southern Chinese populations, 21-23 and in women in an eastern Chinese population. 24 Our study added to the evidence that non-HDL cholesterol could be a better predictor of diabetes than total, HDL, and LDL cholesterols in the Ethiopian population.…”
Section: Discussionmentioning
confidence: 76%